The Determination of Metallization Degree of Pre-reduced Chromite with Image and Rietveld Analysis - Leino, Teemu; Taskinen, Pekka A.; Eric, Hurman (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Metallization degree of pre-reduced chromite samples was determined using two methods. The chromite samples were reduced in the solid state by the use of methane-hydrogen gas mixtures. First method was image analysis of micrographs obtained by scanning electron microscope where heavier metallic phases appear as bright white areas which are relatively easy to segment using a thresholding algorithm. The second technique was Rietveld analysis of X-ray powder diffraction pattern which fits a calculated profile onto a measured X-ray diffraction pattern to gain information about phase quantities. Rietveld refinement and phase composition analysis was performed with PANalytical’s X’Pert HighScore Plus program from the XRPD (X-ray powder diffraction) data. The results from both techniques were in good agreement. Metallization degrees for the investigated samples ranged from 15 to 65 percent depending on the extent of reduction which was a function of time, reduction temperature and methane content of the gas mixture. These results are promising and show that either image analysis or X-ray Rietveld analysis can be used as a relatively fast method to determine the degree of metallization of pre-reduced samples in comparison to the slow and tedious chemical analysis.